Giant metastasizing malignant hidradenoma in a child - Sunil K Bajaj; Ritu Misra; Rohini Gupta; Anju Bansal (Indian Dermatology Online Journal, 2016)
An 8-year-old girl presented with a scalp swelling. The swelling was recurrent, reappearing everytime after local excision. She underwent surgery and the histopathologic diagnosis was malignant hidradenoma. This very rare and aggressive tumor is known to occur in elderly population and is histopathologically distinct from its commonly occuring benign counterpart. Malignant hidradenoma is resistant to chemotherapy and radiotherapy. We empahsize that being cognizant of the possibility of this rare tumor would assist in timely action in the form of wide resection, with possible reduction in morbidity and mortality.